Assortment structure in beech coppice stands in the Crni vrh region - Danilović Milorad; Krstić Milun; Pantić Damjan; Matović Bratislav (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2003)
Assortment structure in beech coppice stands was studied for the region of Crni vrh. Assortment structure was determined according to the standard (JUS) in two ecological units. The study results show that the assortment value structure significantly increases with the increase of tree diameter and that there are no statistically significant differences in assortment structure between the selected ecological units. The dependence of the assortment value structure on tree diameter can be represented by an exponential function. The value percentage of assortments made of stem wood in theoretical crosscutting depending on tree diameter has an increasing tendency, except for the wood for excelsior.